An In-Vivo Study of Sonodynamic Therapy with Encapsulated Hematoporphyrin - Shukufeh Souri; Majid Jadidi; Hadi Hasanzadeh; Tahereh Khani; Vahid Semnani (Frontiers in Biomedical Technologies, 2022)
Purpose: According to the side effects of invasive cancer treatments, Sonodynamic Therapy (SDT) as a noninvasive method for breast adenocarcinoma was considered. Sonosensitizer agents’ encapsulation can improve the accumulation of these drugs in the tumor tissue and reduce treatment side effects. Hence, mice breast adenocarcinoma SDT with Hematoporphyrin (HP) and HP-encapsulated Mesoporous Silica Nanoparticles (HP-MSNs) was carried out.